P28 Decreased platelet size in systemic lupus erythematosus is associated with up-regulation of type I interferon proteins. (23rd March 2020) - Linge, Petrus; Wirestam, Lina; Arve, Sabine; Kahn, Robin; Jönsen, Andreas; Bengtsson, Anders
Abstract : Background: Dysregulated apoptosis is of major importance in Systemic Lupus Erythematosus (SLE) pathogenesis, linked to the development of autoantibodies, immune complex formation and type I interferon signaling. Platelets from SLE patients are smaller in size, compared to platelets from healthy individuals, which may suggest an increased rate of apoptosis, a known cause of platelet shrinkage. Our aim with this project was to investigate if decreased platelet size could be explained by increased apoptosis rates. Methods: Platelet activation markers; CD62P, CD41, CD154, CD32, PAC-1 and PAR1 and apoptosis; Annexin V, Caspase 3 activation, mitochondrial content (MitoTracker) and mitochondrial depolarization (JC-1) where analyzed in 23 SLE patients and 10 healthy controls (HC) by flow cytometry. Analysis of the total protein content in platelets from SLE patients of normal (n=5) and decreased (n=5) size were made using mass spectrometry (MS). Results: The level of CD41 (p=0.001) positive platelets and mean expression of CD154 (p=0.004) were higher in SLE patients. A JC-1 ratio (p=0.0001) indicting increased mitochondrial depolarization was significantly associated with platelets from SLE patients. MS analysis revealed 32 proteins with ≥ 1.5-fold difference and a p-value of less than 0.05 (Abundance Ratio Adjusted). STAT1, ISG15, NMI and TRIM25 were among 19 proteins expressed at higher levels in small platelets and unbiased enrichments analyses showed a significant overrepresentation of proteins related to type I interferon signaling. Conclusions: The increased mitochondrial depolarization in platelets from SLE patients is an indication but not conclusive evidence of increased platelet apoptosis. Interestingly, decreased sized platelets from SLE patients showed an up regulation of type I interferon related proteins, suggesting direct or indirect influence of IFN. This is a novel finding that may suggest that platelet size is related to IFN signaling. Further studies will be conducted to investigate the mechanistic and potential clinical role of this finding.